Educación para la sostenibilidad desde la resolución de problemas energéticos en la física para ingenieros - Machín-Armas, Francisco Octavio; Fernández Santiesteban, Eduardo; Ferras Santiesteban, Elser; Fernández Calzadilla, Eduardo (Góndola, enseñanza y aprendizaje de las ciencias, 2025)
The issue of the sustainable use of energy is current, due to the environmental, climate, energy and global development crisis. On the other hand, problem solving for science teaching has gained relevance in recent decades, which has significance in the learning of Physics for students of different engineering fields. In this direction, the article addresses the scientific problem related to how to promote the education of the environmental attitude, assessment of sustainability for students of these careers, to which an answer is sought in the problematization of the teaching-learning process and this, from the resolution of physical-energy problems related to sustainable energy development. In the article, through the logical-historical method and the bibliographic review, an epistemological study is carried out of the evolution of the conception of sustainability and education in sustainability science, of attitudes as a psychological formation of personality that determine favorable or negative predispositions. not of the young students to the energy-environmental question, as well as the resolution of physical problems, seen this from the works of Polya of 1945 for Mathematics. Then, from the Didactics of Physics, the treatment of the energy concept and the resolution of problems of this content oriented towards education for the sustainability of development are based. In this sense, the proposal of a resolution method is based on which the assessment of the sustainability of possible solutions is included, to which its viability and effectiveness are experimentally validated through statistical tools and the respective conclusions are offered.